Salivary duct carcinoma with rhabdoid features: a salivary counterpart of pleomorphic lobular carcinoma of the breast. Issue 2 (8th June 2016) - Kusafuka, Kimihide; Kawasaki, Takuya; Maeda, Matsuyoshi; Yamanegi, Koji; Baba, Satoshi; Ito, Yohei; Inagaki, Hiroshi; Nakajima, Takashi
Abstract : Aim: To analyse the clinicopathological features and immunohistochemical characteristics of nine cases of salivary duct carcinoma (SDC) with rhabdoid features (SDCRF), representing a new, extremely rare type of salivary gland malignancy. Methods and results: We analysed 2511 cases of salivary gland tumour, clinicopathologically and immunohistochemically. The incidence of SDCRF was 0.4%. Eight patients were male. The age of patients ranged from 36 years to 85 years (mean, 61 years). SDC arose from the parotid glands and submandibular gland in six and three cases, respectively. Seven cases appeared as a carcinoma component of carcinoma ex pleomorphic adenoma cases. Six patients died of disease. Histologically, diffuse proliferations of non‐coherent large ovoid or polygonal carcinoma cells with eosinophilic cytoplasm and eccentric nuclei were observed in all cases; such cytological characteristics were defined as 'rhabdoid features'. Immunohistochemically, all cases were positive for cytokeratin, gross cystic disease fluid protein‐15, androgen receptor, and SMARCB1, seven cases were positive for HER2, and two cases were positive for epidermal growth factor receptor. However, all cases were negative for vimentin and myoepithelial markers. Eight cases showed no or aberrant expression of E‐cadherin and β‐catenin. The results suggest that SDCRF is an extremely rare subtype of SDC, and not a sarcomatoid variant of SDC. SDCRF is histologically unique, and is positive for SDC markers but negative for vimentin, unlike rhabdoid‐type carcinomas arising from other organs. Conclusions: The morphogenesis of SDCRF is related to no or aberrant expression of cell–cell adhesion molecules. Therefore, SDCRF could be a salivary counterpart to pleomorphic lobular breast carcinoma.